FUNGSI KOMUNIKASI PENYULUH DALAM MENINGKATKAN HASIL PANEN PADI PADA PETANI SAWAH KECAMATAN BUNGARAYA KABUPATEN SIAK SRI INDRAPURA - Abdus Salam Firmansyah; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The background of this research with the problems faced by farmers in increasing rice yields which farmers are farmers from the local area who have an average level of know ledge that is low. The problem faced by farmers as a way of processing the soil is good ang right as well the use of drugs for the plant, the government helps farmers problems with the procurement of agricultural extension workers in the region who are in the department of technical implementation unit (UPTD) agriculture. This study uses a qualitative method of data collection techniques participant observation, interviews, an documentation. Subjects in this study were agricultural extension and rice farmers in the village Bungaraya. Whereas the object of research is the communication function extension unit technical implementing agency (UPTD) Bungaraya agricultural districs. To analyze the collected data the authors used an interactive model analysis. The final stage of this analysis is examining the validity of the data. The results of research, extension communication function in society is indispensable in helping to increase knowledge of farmers in improving their rice yields. With the presence of extension can bring considerable impact, which before the role of extension workers how much land management that is incompatible with science is taught by the extension through agricultural extension methods. In practice in the village Bungaraya its extension accomplished by using the system of training and visits (CONDUCT), demonstration plots (Pilot), and a field school. The method can produce a feed-back and the rate of adaption of counseling objectives can be achieved despite the persistence of the constraints and obstacles in extension activities. While in the manufacturing extension program, extension assisted by the chairman of farmer groups and programs will be made has previously been adapted to the circumstances in the field of information obtained by farmers and farmer groups. As for the factors that become obstacles in extension activities such as internal and external factors for the extension, the language factor, time, education of farmers, farmers awareness in extension activities and still lack of motivation of farmers in extension. Keywords : Communication Extension, Technical Implementation Unit Services (UPTD) Agriculture